Bireysel Emeklilik Sisteminin Kamu Finansmanına Etkileri - (:unkn) unknown (My University, 2019)
Dağıtım tabanlı geleneksel sosyal güvenliksisteminde yaşanan ve yaşanması muhtemel sorunlardandolayı, geleneksel sisteme gerek alternatifgerek yardımcı olması adına fonlama tabanlıbireysel emeklilik sistemine geçişin hızlandığıgünümüzde, bireysel emeklilik sisteminin ülkemizdekigelişimi ve bu gelişim sürecinde sistemdetoplanan ve yatırıma yönlendirilecek fonların,makro bazda sermaye piyasalarına mikro bazdaise kamu finansmanına olan etkilerine ilişkin değerlendirmeleraşağıda yapılmıştır.

Due to problems experienced and possible problems in the traditional social security system based on distribution, Nowadays, the transition to the funding-based Individual Retirement System accelerate, in order to both the alternative and support,The development of the Individual Retirement System in Turkey and the effects of the funds collected and directed investment in Individual Retirement System in this development process to the capital markets on the macro basis and to the public finance on micro base are given below.
THE EFFECTS OF INDIVIDUAL RETİREMENT SYSTEM ON PUBLIC FINANCE